2019
DOI: 10.1016/j.heliyon.2019.e02987
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxide reduction through absorbent solutions containing nitric acid and hydrogen peroxide in hollow fiber membrane modules

Abstract: Emissions of nitrogen oxides such as NO and NO2, which are commonly known as NOx, are threats to human existence and cause environmental problems. Mainly, two techniques have been developed to drastically reduce these emissions, which are dry and wet processes. The wet process has several advantages, major identifiable advantages are the adaptability to the flue gas, low operating temperatures and no poisoning and inactivation catalyst. Also, a mixture of hydrogen peroxide and nitric acid are used as absorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 33 publications
4
23
0
1
Order By: Relevance
“…It should be noted that a single ceramic fiber membrane was used in this study, so the overall reduction efficiencies are not as high as those reported by Kartohardjono et al [33]. The size of hollow fiber varies greatly, and the removal efficiency per fiber cannot be compared.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…It should be noted that a single ceramic fiber membrane was used in this study, so the overall reduction efficiencies are not as high as those reported by Kartohardjono et al [33]. The size of hollow fiber varies greatly, and the removal efficiency per fiber cannot be compared.…”
Section: Resultsmentioning
confidence: 78%
“…Denitration was performed in a ceramic HFMC with surface modification. Kartohardjono et al [33] conducted a similar study. They assessed NO reduction performance using 50-150 fibers in an HFMC module, but the provided values were insufficient to compare.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Various technologies have been developed to reduce the NOx concentration in the air. These technological developments include dry methods such as Selective Catalytic Reduction & Selective Non-catalytic Reduction (Brandenberger, Kröcher, Tissler, & Althoff, 2008;Cheng & Bi, 2014;Jug, Homann, & Bredow, 2004;Roy & Baiker, 2009), and wet methods such as absorption using absorbents (Fangyang, Jiali, Wei, Jiyun, & Jianfeng, 2020;Kartohardjono, Merry, Rizky, & Pratita, 2019). The SCR method uses NH3 as a reducing agent over catalysts based on V2O5-WO3/TiO2 or Cu-and Fe-zeolite, which is very efficient to reduce NOx but requires high temperatures around 300 to 400 °C (Grossale, Nova, & Tronconi, 2008;Mehring, Elsener, & Kröcher, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 49% of NOx comes from motor vehicles, 27% comes from the activities of the electricity generation industry, and 19% comes from household activities. NOx has also been reported to have the ability to cause acid rain, form fog fumes, decrease water quality, destroy ecosystems, and contribute to global warming (Choi et al, 2014;Gao et al, 2018;Kartohardjono et al, 2019a;Sun et al, 2019). In addition, NOx is also having harmful effect on the human being (Kartohardjono et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%